Effect of INIAP 811 and Tithonia diversifolia on in vitro nutritional value - Conrado-Palma, Diego Javier (2022)
The aim of this study was to evaluate the inclusion of INIAP 811 grass and Tithonia diversifolia in five proportions (100:0, 75:25, 50:50, 25:75, 0:100 respectively on dry basis), on the bromatological composition, in vitro digestibility and in vitro gas production in the dry season. The treatments were T1= 100% grass INIAP 811; T2= 75% INAP 811 grass and 25% T. diversifolia; T3= 50% INAP 811 grass and 50% T. diversifolia; T4= 25% INAP 811 grass and 75% T. diversifolia and T5= 100% T. diversifolia. The variables for the bromatological composition: dry matter (DM), organic matter (OM), crude protein (CP), neutral detergent fiber (NDF) and acid detergent fiber (ADF). For in vitro dry matter digestibility (IVDMD), neutral detergent fiber (NDF) and acid detergent fiber (ADF). In vitro gas production from dry matter (B) and gas production rate (C). The best (p<0.05) DM was reported by T1 (90.18%), OM, CP, NDF and ADF were recorded by T5 (90.18; 22.19; 48.11 and 32.24%). respectively). The highest (p<0.05) IVDMD, NDF and ADF was reported by T5 (70.00, 65.77 and 44.69%, respectively). The lowest (B) (p<0.05) was reported by T5 (204.05 mL gas) and the highest (c) (0.050% h). The inclusion of Tithonia diversifolia influenced the bromatological composition, digestibility and in vitro gas production, noting a greater efficiency of this forage as the evaluated proportions increased